Urban green spaces: social cohesion, human health, and Islamic green city / Abdul Rahman Hatta ... [et al.] - Hatta, Abdul Rahman; Abd Jalil, Nurul Amira; Jimi Sham, Rashidah; Hamidi, Mohd Hazwan (UiTM Press, 2024)
Sustainable development has become top priority for many countries in their urban development plans in responding to climate changes. Green dimension is a critical aspect of pursuing sustainability in urban development. Copenhagen, Denmark, is one of the leading cities adopted the green city concept to achieve sustainability. As the world's most populous Muslim-majority country, Indonesia also started to adopt the green city concept in its current development of new capital city to address environmental problems. Based on these two (2) examples, this study is intended to examine the importance of urban green spaces (UGS) within urban context and its benefit to the inhabitants. This study delves into the narrative of Islamic views on natural and urban environments based on the principles of sustainability in the Qur’an and Hadith. The result of this study will briefly outline the concept of Urban Green Space (UGS) from Islamic perspective. The case study examination will be used to access the theoretical review found with the actual condition on ground. The examples are adopted from the government initiative of Islamic Green City approach.